Surgical, oncologic, and obstetric outcomes of radical trachelectomy in early-stage cervical cancer: results from a retrospective cohort study at Brazil National Cancer Institute - Bellotti, José Augusto; Gutierres, Isabella Gonçalves; Furtado, Yara Lúcia; Patury, Patricia; Figueiredo, Juliana de Almeida; Guitmann, Gustavo; Fiorelli, Rossano Keppler Alvin; da Silva, Fernanda Campos (Frontiers in Oncology, 2024)
Objective: to analyze oncological, obstetrical, and surgical results of young early-stage cervical cancer patients who underwent radical trachelectomy (RT) surgery and wished to maintain their fertility. Methodology: a retrospective cohort study was carried out concerning cases attended at the Brazilian National Cancer Institute Gynecology Oncology Service. Patients who underwent RT between January 2005 and January 2021 were included. Results: A total of 32 patients with median age of 32 years old, 62.5% of whom were nulliparous, were assessed. Concerning cancer type, 65.6% squamous cell carcinoma (SCC) cases, 31.2% adenocarcinoma cases and 3.1% adenosquamous carcinoma cases were verified. Stage IA2 was evidenced in 12.5% of the patients and stage IB < 4 cm in 87.5%. Regarding surgical approaches, 68.25% of the patients underwent vaginal RT (VRT), 18.75%, abdominal RT (ART), 9.3%, the robotic radical trachelectomy (RORT) and 3.1%, video laparoscopy radical trachelectomy (VLRT). The median number of removed lymph nodes was 14, with only two detected as positive. Two cases of positive surgical margins were noted. A total of 3.1% intraoperative and 31.25% postoperative complications were observed, with cervical stenosis being the most common. The recurrence rate of the study was 3.1%, with a median follow-up time of 87 months, where 3.1% deaths occurred. The pregnancy rate of the study was 17.85% (5/28), with 54.5% evolving to live births and 45.5% evolving to abortion. Conclusion: Radical trachelectomy is a feasible procedure presenting good oncological results and acceptable pregnancy rates.